Azure for architects : implementing cloud design, DevOps, containers, IoT, and serverless solutions on your public cloud - Modi, Ritesh (Packt Publishing, 2019)
"Azure is evolving at a rapid speed and introducing newer services almost every week. What was relevant a year back is not more relevant today as better services are available to solve the same challenges. This book will provide architects with solid information about the important services for hosting, deploying and architecting solutions."--Provided by publisher